Clinical aspects in patients with pulmonary infection caused by mycobacteria of the Mycobacterium abscessus complex, in the Brazilian Amazon - Monteiro, José Tadeu Colares (J Bras Pneumol, 2018)
OBJECTIVE: To describe the clinical manifestations of patients with pulmonary infection caused by mycobacteria of the Mycobacterium abscessus complex (MABSC), and to compare these manifestations with those of patients infected with other nontuberculous mycobacteria (NTM). METHODS: This was a retrospective cohort study involving 43 patients divided into two groups: the MABSC group, consisting of patients with pulmonary infection caused by MABSC (n = 17); and the NTM group, consisting of patients with pulmonary infection caused by NTM other than MABSC (n = 26). Patients were previously treated with a regimen of rifampin, isoniazid, pyrazinamide, and ethambutol before the diagnosis of NTM was confirmed by two culture-positive sputum samples. The nucleotide sequences of the hsp65, 16S rRNA, and/or rpoB genes were analyzed to identify the mycobacteria. Data were collected on demographic, clinical, and radiological characteristics, as well as on treatment responses and outcomes. RESULTS: Loss of appetite was the only clinical manifestation that was significantly more common in the MABSC group than in the NTM group (p = 0.0306). The chance of having to use a second treatment regimen was almost 12 times higher in the MABSC group than in the NTM group. Treatment success was significantly higher in the NTM group than in the MABSC group (83.2% vs. 17.6%; p < 0.0001). The chance of recurrence was approximately 37 times higher in the MABSC group than in the NTM group. CONCLUSIONS: In the study sample, treatment response of pulmonary disease caused by MABSC was less favorable than that of pulmonary disease caused by other NTM.